Analisis Faktor Yang Mempengaruhi Kualitas Gingivitis Pada Ibu Hamil Di Puskesmas Pujon Malang - Angga An Novita; Sentot Imam Suprapto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: to analyze the influence of gestational age, the level of knowledge of pregnant women about gingivitis and oral hygiene status on gingivitis in pregnant women at the Pujon health center, Malang Regency.Methods: The design of this study is quantitative observational with dependent variables of gingivitis. The independent variabels in this study were gestational age, level of knowledge as well as oral hygiene status. The subjects of the study were pregnant women who met the inclusion and exclusion criteria of 102 people. The study was conducted in the Pujon health center area, Malang regency, for the time period of July-September 2022. The data were analyzed using SPSS software version 25 with ordinal regression tests.Results: The results showed that gestational age did not affect gingivitis with p value=0.061. The level of knowledge affects gingivitis with p value=0.016. Oral hygiene status affects gingivitis with p value=0.000. Gestational age, level of knowledge, oral hygiene status simultaneously influenced gingivitis p value=0.001, with a large influence of 32.9%.Conclusion: Simultaneously the gestational age, level of knowledge, oral hygiene status affect gingivitis in pregnant women at the Pujon health center, Malang regency